Maxillary resection for cancer, zygomatic implants insertion, and palatal repair as single-stage procedure: report of three cases - Pietro Salvatori; Antonio Mincione; Lucio Rizzi; Fabrizio Costantini; Alessandro Bianchi; Emma Grecchi; Umberto Garagiola; Francesco Grecchi (SpringerOpen, 2017)
Abstract Background Oronasal/antral communication, loss of teeth and/or tooth-supporting bone, and facial contour deformity may occur as a consequence of maxillectomy for cancer. As a result, speaking, chewing, swallowing, and appearance are variably affected. The restoration is focused on rebuilding the oronasal wall, using either flaps (local or free) for primary closure, either prosthetic obturator. Postoperative radiotherapy surely postpones every dental procedure aimed to set fixed devices, often makes it difficult and risky, even unfeasible. Regular prosthesis, tooth-bearing obturator, and endosseous implants (in native and/or transplanted bone) are used in order to complete dental rehabilitation. Zygomatic implantology (ZI) is a valid, usually delayed, multi-staged procedure, either after having primarily closed the oronasal/antral communication or after left it untreated or amended with obturator. The present paper is an early report of a relatively new, one-stage approach for rehabilitation of patients after tumour resection, with palatal repair with loco-regional flaps and zygomatic implant insertion: supposed advantages are concentration of surgical procedures, reduced time of rehabilitation, and lowered patient discomfort. Cases presentation We report three patients who underwent alveolo-maxillary resection for cancer and had the resulting oroantral communication directly closed with loco-regional flaps. Simultaneous zygomatic implant insertion was added, in view of granting the optimal dental rehabilitation. Conclusions All surgical procedures were successful in terms of oroantral separation and implant survival. One patient had the fixed dental restoration just after 3 months, and the others had to receive postoperative radiotherapy; thus, rehabilitation timing was longer, as expected. We think this approach could improve the outcome in selected patients.